2018
DOI: 10.1248/cpb.c18-00450
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Stability of Amorphous Tadalafil and Four Crystalline Polymorphs

Abstract: Tadalafil (TD), a phosphodiesterase-5 (PDE-5) inhibitor with poor oral bioavailability. The aim of the study was to prepare and characterize three crystalline polymorphs of TD (II, III, and IV) and the tadalafil amorphous form (TD-AM). TD polymorphs and TD-AM were prepared and characterized by polarized light microscope (PLM), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), X-ray powder diffractometry (XRPD), and Fourier-transform (FT)IR, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Briefly, 200 mg of tadalafil was dissolved in a solvent mixture comprising of 20 mL of methanol, 25 mL of acetonitrile and 25 mL of dichloromethane, followed by rotary vacuum evaporation at 40–45 °C in a water bath. 35 Amorphous repaglinide was obtained by rotary evaporation of repaglinide acetone solution (∼10 mg mL −1 ) under 55 °C. 36 The solid residue in the flask was collected and vacuum-dried for 24 h at room temperature to remove the residual solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 200 mg of tadalafil was dissolved in a solvent mixture comprising of 20 mL of methanol, 25 mL of acetonitrile and 25 mL of dichloromethane, followed by rotary vacuum evaporation at 40–45 °C in a water bath. 35 Amorphous repaglinide was obtained by rotary evaporation of repaglinide acetone solution (∼10 mg mL −1 ) under 55 °C. 36 The solid residue in the flask was collected and vacuum-dried for 24 h at room temperature to remove the residual solvents.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Fig. 9, Tadalafil had a sharp melting point (TM) at 303°C [38,39]. Thermal stability of Tadalafil and its binary mixtures with different excipients are presented in the Table 2.…”
Section: Resultsmentioning
confidence: 96%
“…Form III is more soluble than form I and dihydrate, while the AUC value of form I is larger than AUC value of form III and dihydrate, which may result from the faster transformation of form III to dihydrate in gastrointestinal fluids, causing a reduction of dissolution rate [23]. Another study revealed that tadalafils polymorphic forms II, III, and IV show significantly lower dissolution and dissolution rates than the amorphous form of the API [24]. Polymorphic form II of tibolone is statically more soluble in water, 0.01 mol L −1 HCl and pH 4.5 acetate buffer.…”
Section: Resultsmentioning
confidence: 99%